Risk exposure, risk-bearing capacity, and risk-coping strategies: a comparative study among urban households in Malaysia - Abdullah Yusof, Selamah; Wan Jusoh, Wan Jamaliah; Abd. Rokis, Rohaiza (EBES Publications, 2013)
Household debt in Malaysia has been on an upward trend and increasing at a relatively fast pace. This study provides an in-depth analysis of the current Malaysian urban households’ vulnerabilities and risks and determines differences across the three major ethnic groups of Malay, Chinese and Indian. It examines households’ perception of risk, their capacity to bear risk, and their coping strategies. The study finds that Malaysian urban households are somewhat vulnerable and more so among the Malay households. Households perceive their exposure to small shocks to be somewhat likely, with Malay households’ rating the likelihood to be higher than others. It is found that 6.2% of the households were not able to deal with a small shock, while more than 20% were unable to cope with a large shock. Households will resort to using their savings or cutting down daily expenditure, or turn to family and friends in coping with financial shocks. Malay households have less and fewer sources of funds in meeting unexpected financial needs. Asset poverty among households is high in which 22.9% can survive on basic necessities for only less than three months if their household income is cut-off, and it is more prevalent in Malay households.